Perspectives of education in teachers of the Faculty of Psychology and Therapy of Human Communication of the Juarez University of the State of Durango - Santiesteban Contreras, María Tereza (Consorcio de Universidades Mexicanas A.C., 2018)
The research intends to show the process that a representative sample of teachers from the Faculty of Psychology and Human Communication Therapy of the Juárez University of the state of Durango has. Furthermore, it searches for significant differences among the teachers ́ perspectives depending on the variables of antiquity and academic degree. For this purpose, a quantitative methodology based on the application of the Teaching Perspectives Inventory was used. The objective of the instrument was to identify the perspectives of teaching from three dimensions: Beliefs, Purposes and Actions of the teachers when they teach. Pating from these three perspectives, there are five dimensions: transmission, learning, development, accompaniment and social reform. According to the results, it was concluded that there is no uniformity in the beliefs of the teachers regarding tuition in contrast with antiquity and level of studies. Nevertheless, these differences were not statistically significant.